2022
DOI: 10.1507/endocrj.ej22-0426
|View full text |Cite
|
Sign up to set email alerts
|

Effects of undernutrition and low energy availability on reproductive functions and their underlying neuroendocrine mechanisms

Abstract: It has been well established that undernutrition and low energy availability disturb female reproductive functions in humans and many animal species. These reproductive dysfunctions are mainly caused by alterations of some hypothalamic factors, and consequent reduction of gonadotrophin-releasing hormone (GnRH) secretion. Evidence from literature suggests that increased activity of orexigenic factors and decreased activity of anorexigenic/satiety-related factors in undernourished conditions attenuate GnRH secre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 126 publications
0
1
0
Order By: Relevance
“…Notably, the nutritional properties of adiponectin may elucidate the mechanisms behind this phenomenon, as AdipoQ is involved in the regulation of hypothalamic energy expenditure, thermogenesis ( Qi et al, 2004 ) and food intake ( Kubota et al, 2007 ), and elevated serum AdipoQ levels are associated with weight loss ( Arita et al, 1999 ). It is well-established that energy status augments or impairs reproductive capacity by regulating GnRH secretion ( Valle et al, 2019 ; Patel and Smith, 2020 ; Iwasa et al, 2022 ). Furthermore, we found that AdipoQ affects reproduction-related receptor genes (ER, PR).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the nutritional properties of adiponectin may elucidate the mechanisms behind this phenomenon, as AdipoQ is involved in the regulation of hypothalamic energy expenditure, thermogenesis ( Qi et al, 2004 ) and food intake ( Kubota et al, 2007 ), and elevated serum AdipoQ levels are associated with weight loss ( Arita et al, 1999 ). It is well-established that energy status augments or impairs reproductive capacity by regulating GnRH secretion ( Valle et al, 2019 ; Patel and Smith, 2020 ; Iwasa et al, 2022 ). Furthermore, we found that AdipoQ affects reproduction-related receptor genes (ER, PR).…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that reproductive function and energy balance are closely linked in most species [1][2][3]. Low energy availability, such as that associated with undernutrition and obesity, disturbs female reproductive function, and some central and peripheral factors are known to affect these changes; for example, the upregulation of hypothalamic appetiteregulatory factors, such as orexin and neuropeptide-Y (NPY), suppresses gonadotrophinreleasing hormone (GnRH) secretion.…”
Section: Introductionmentioning
confidence: 99%